2023
DOI: 10.1371/journal.pgph.0001288
|View full text |Cite
|
Sign up to set email alerts
|

Household waste sorting practice, and factors associated with sorting practice in Bedelle town, Southwest Ethiopia

Abstract: Household solid waste generation rate in low-income countries is increasing due to population growth and changes in people’s lifestyles. Sorting waste into categories is an important step in household waste management. However, there is limited information about sorting practices in a low-income setting like Ethiopia. Therefore, this study aimed to assess household solid waste (HSW) sorting practices, and factors associated with sorting practices.A community-based cross-sectional study was conducted from April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Men play a role in transporting and processing plastic waste into plastic raw materials of economic value. Donacho et al (2023) revealed that women are around 88% more likely to sort waste in the household compared to men. Women in the household are the main decision-makers in the household responsible for the waste of family disposal practices (Patel et al, 2018).…”
Section: Behavior In Sorting Household Wastementioning
confidence: 99%
“…Men play a role in transporting and processing plastic waste into plastic raw materials of economic value. Donacho et al (2023) revealed that women are around 88% more likely to sort waste in the household compared to men. Women in the household are the main decision-makers in the household responsible for the waste of family disposal practices (Patel et al, 2018).…”
Section: Behavior In Sorting Household Wastementioning
confidence: 99%